IN VIVO INTERACTION OF PROPYLTHIOURACIL WITH SODIUM IODIDE (Na131I) RADIOPHARMACEUTICAL IN RATS (Rattus norvegicus) - Isti Daruwati; Iim Halimah; Isa Mahendra; Dwi Deasy F; A. Hanafiah WS (Jurnal Sains dan Teknologi Nuklir Indonesia (Indonesian Journal of Nuclear Science and Technology), 2017)
IN VIVO INTERACTION OF PROPYLTHIOURACIL WITH SODIUM IODIDE (Na131I) RADIOPHARMACEUTICAL IN RATS (Rattus norvegicus).. The aim of this research is to determine the effect of propylthiouracil (PTU) treatment to pharmacokinetics interaction and biodistribution profile of Na131I radiopharmaceuticals. Three groups of animal model were used in this experiment, i.e. experimental animals which given PTU for 1 time (onset or A groups), PTU for six days (B Groups) and without treatment (control or C Groups). Pharmacokinetics and biodistribution test were conducted by giving PTU per oral and  after 24 hours, continued by giving Na131I solution per oral. In pharmacokinetics test, percentage of injection dose/gram of blood (%ID/g) was calculated to determine the absorption, distribution and elimination half time. In biodistribution test, percentage of injection dose/gram of organs was calculated to determine the accumulation of Na131I in spesific organs. The results showed that the absorption half time of A, B and C groups were 3.14 ± 1.42, 2.49 ± 0.49 and 2.52 ± 0.7 hours, respectively. The distribution half time of A, B and C groups were 10.58 + 5.85, 12.92 + 3.75 and 11.42 + 3.15 hours, respectively. The elimination half time of A, B and C groups were 113.03 + 46.03, 96.57+ 47.76 and 196.71 + 145.21 hours, respectively. Biodistribution test results showed that the accumulation of Na131I in thyroid of A, B and C groups were 1.31 + 0.45, 5.03 + 0.55 and 4.45 + 2.24 % respectively. This research was concluded that PTU treatment cannot alter absorption, distribution and elimination half time Na131I, but the accumulation in thyroid was decrease in A group to control.